THE IMPACT OF USING INFLUENCER ON CONSUMER PURCHASE INTENTION WITH ATTITUDE TOWARDS INFLUENCER AND BRAND ATTITUDE AS MEDIATOR - Immanuel, Dewi Mustikasari; S., Alexandria Bianda H. (Jurnal Aplikasi Manajemen, 2021)
This study is conducted to determine the effect of perceived credibility, trust, experience, and attractiveness as an evaluator of influencers' effectiveness on consumer purchase intention in fashion products mediated by attitude towards influencers and brand attitude. Influencers are those who regularly share content related to certain fields or skills on social media platforms. This study is based on the Theory of Planned Behavior (TPB) and other previous studies related to influencers' effectiveness on purchase intention of fashion products. The population in this study is 385 women in Surabaya with a non-probability sampling method using a purposive sampling technique. The data analysis method used in this study is Structural Equation Modeling-Partial Least Square (SEM PLS) with a smart PLS 3.0 program. The analysis results in this study show that perceived credibility, trust, and attractiveness have a positive and significant effect on attitude towards influencers. In contrast, perceived expertise has a negative and insignificant impact on attitude towards influencers. Attitude towards influencers fully mediates the influence of perceived credibility, trust, and attractiveness on brand attitude and purchase intention. Brand attitude fully mediates the influence of attitude towards influencers on purchase intention. In this study, variable perceived expertise used did not affect attitude towards influencer variables. This is different from previous studies that have been done before. For further researchers, it is suggested that they can again use perceived expertise and other variables that can support more deep assessments that give rise to consumer attitudes towards an advertisement made by fashion product influencers in subsequent studies using different populations. The analysis model that has been used in this study can then be reused in conducting further research with varying numbers of populations and types.